Lower brain-derived neurotrophic factor levels associated with worsening fatigue in prostate cancer patients during repeated stress from radiation therapy. (16th November 2016) - Saligan, L.N.; Lukkahatai, N.; Holder, G.; Walitt, B.; Machado-Vieira, R.
Abstract : Objectives. Fatigue during cancer treatment is associated with depression. Neurotrophic factors play a major role in depression and stress and might provide insight into mechanisms of fatigue. This study investigated the association between plasma concentrations of three neurotrophic factors (BDNF, brain-derived neurotrophic factor; GDNF, glial-derived neurotrophic factor; and SNAPIN, soluble N -ethylmaleimide sensitive fusion attachment receptor-associated protein) and initial fatigue intensification during external beam radiation therapy (EBRT) in euthymic non-metastatic prostate cancer men. Methods. Fatigue, as measured by the 13-item Functional Assessment of Cancer Therapy-Fatigue (FACT-F), and plasma neurotrophic factors were collected at baseline (prior to EBRT) and mid-EBRT. Subjects were categorized into fatigue and no fatigue groups using a > 3-point change in FACT-F scores between the two time points. Multiple linear regressions analysed the associations between fatigue and neurotrophic factors. Results. FACT-F scores of 47 subjects decreased from baseline (43.95 ± 1.3) to mid-EBRT (38.36 ± 1.5, P < 0.001), indicating worsening fatigue. SNAPIN levels were associated with fatigue scores ( r s = 0.43, P = 0.005) at baseline. A significant decrease of BDNF concentration ( P = 0.008) was found in fatigued subjects during EBRT ( n = 39). Conclusions. Baseline SNAPIN and decreasing BDNF levels may influence worsening fatigue during EBRT. Further investigations are warranted to confirm their role in the pathophysiology and therapeutics of fatigue.